Estudio del sistema de alcantarillado sanitario - pluvial y tratamiento de aguas residuales para la parroquia Torata, cantón Santa Rosa, provincia de El Oro. - Arias Yánez, Darwin Lenin (2015)
The absence of a system of sanitary and storm sewers in the parochial head Torata the canton Santa Rosa, threatens the health of its people and allows the spread of diseases, and consequently pollutes the environment. Aiming is planned to provide this service sector sanitary, storm sewer and wastewater treatment to solve the problems of poor health and thereby improve their standard of living and development. To use this research modality literature review, documentary, online consultations, with the support of field research such as surveys, land surveying, soil studies.